A comprehensive floristic knowledge of a fragment of Semideciduous Seasonal Forest [Parque Estadual da Serra da Concórdia], Rio de Janeiro, Brazil - Deccache, Lara Serpa Jaegge; Mynssen, Claudine Massi; Fraga, Claudio Nicoletti de; Fernandez, Eduardo Pinheiro; Guimarães, Elsie Franklin; Lírio, Elton John de; Filardi, Fabiana Luiza Ranzato; Fraga, Fernanda Ribeiro de Mello; Saleme, Fernanda; Shimizu, Gustavo Hiroaki; Lima, Haroldo Cavalcante de; Ogasawara, Helen Ayumi; et al. (Pensoft Publishers, 2024)
Background The “Serra da Concórdia” is part of the Atlantic Forest phytogeographical domain in the Brazilian state of Rio de Janeiro and it has a predominant phytophysiognomy of Semideciduous Seasonal Forest. This region underwent intense habitat loss and fragmentation during the 19th century, due to coffee plantations and later pastures. With the decline of these activities, the areas were abandoned, triggering secondary succession. In 2002, the “Parque Estadual da Serra da Concórdia was established in this region to preserve the remaining forest fragments. The updated list of vascular plants recorded in this protected area, published in the “Catálogo de Plantas das Unidades de Conservação do Brasil”, is presented here, along with information on richness, endemism, and conservation status. New information The “Parque Estadual da Serra da Concórdia houses 231 vascular plant species, of which 90% are angiosperms, 10% ferns and lycophytes, and 27% endemic to the Atlantic Forest. Ten species are threatened with extinction, three are categorized as Endangered, and seven as Vulnerable. Although there have been expeditions in the “Parque Estadual da Serra da Concórdia”, they have been limited, resulting in a low number of records and the species richness for a protected area. This is notable considering the 2, 130 Brazilian native vascular plant species recorded in the semideciduous seasonal forest of Rio de Janeiro. Our data indicates that floristic inventories of Brazilian protected areas could help highlight gaps in flora knowledge and support the proposal of effective conservation actions.
Keywords: Catálogo de Plantas das Unidades de Conservação do Brasil; Conservation; Protected Areas; Semideciduous Seasonal Forest